Islamic Leadership And Maqasid Al-shari'ah: Reinvestigating The Dimensions Of Islamic Leadership Inventory (ILI) Via Content Analysis Procedures - Mahazan Abdul Mutalib @ Talib; Wan Mohd Fazrul Azdi Wan Razali; Mohd Rumaizuddin Ghazali; Yuseri Ahmad; Mohd Rosmizi Abd Rahman; Khairunneezam Mohd Noor; Nurhafizah, S.; Rozita, A.; Siti Aishah, H.; Muhammad, H.; Mohd. Azhar, I.R.; Abdullah, A.G.; et al. (OCERINT, 2024)
Non-Indexed Publication